2015
DOI: 10.17795/zjrms1017
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Aqueous and Ethanolic Extracts of Satureja Bachtiarica on Some Pathogenic Bacteria in Vitro

Abstract: Background: Essences and extracts of herbs, possess a variety level of biological activities, in addition the antimicrobial activities of a large number of these have been proved. With regard to the biologically active compounds and traditional use of the Satureja bachtiarica, it seems that this plant has significant antimicrobial effects. Objectives: The aim of this study is to evaluate the antimicrobial effect of aqueous and ethanolic extracts of S. bachtiarica against Enterobacter aerogenes, Bacillus subtil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These results showed that aqueous extract had the inhibitory effect on Enterococcus faecalis merely in 480 and 960 mg/mL concentrations. Similarly, Heidari-Sureshjani et al [17] found aqueous extract of S. bachtiarica at 60 and 80 mg/mL had the inhibitory effect on Enterobacter aerogenes, however, 20 and 40 mg/mL have no significant antimicrobial effect on E. aerogenes. These findings may be due to the choice of extraction method which is applied for extracting the active compounds.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These results showed that aqueous extract had the inhibitory effect on Enterococcus faecalis merely in 480 and 960 mg/mL concentrations. Similarly, Heidari-Sureshjani et al [17] found aqueous extract of S. bachtiarica at 60 and 80 mg/mL had the inhibitory effect on Enterobacter aerogenes, however, 20 and 40 mg/mL have no significant antimicrobial effect on E. aerogenes. These findings may be due to the choice of extraction method which is applied for extracting the active compounds.…”
Section: Discussionmentioning
confidence: 91%
“…Heidari Sureshjani et al 2015 [17] also showed that ethanolic extract of Salvia chorassanica had exhibited broad spectrum activity against Enterobacter aerogenes, Listeria innocua and Bacillus subtilis as compared to aqueous extract. Previous chemical investigations on different species of salvia have shown the presence of flavonoids, diterpenoids, triterpenoids, sesterterpenes, and essential oils exhibits the antitumor, antimicrobial, cytotoxic and anti-inflammatory activities [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies pointed out the impact of natural extract as an antimicrobial agent against harmful microorganisms [ 46 ]. Numerous published research on the antibacterial activity of nanoemulsions against Gram-positive and Gram-negative bacteria [ 47 , 48 ], revealed that nanoemulsions had very little antibacterial impact on gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…[31]. In this regard, another study showed that the MBC of Satureja bachtiarica ethanol extract for Bacillus subtilis and Listeria innocua were 16 and 32 mg/ml, respectively [32]. In a similar study, the extract of this plant at 2 mg / ml concentration had an inhibition effect against Streptococcus pyogenes and Staphylococcus epidermidisat but it did not effect on Pseudomonas aeruginosa [33].…”
Section: Discussionmentioning
confidence: 99%